Networking Pyrolyzed Zeolitic Imidazolate Frameworks by Carbon Nanotubes Improves Conductivity and Enhances Oxygen‐Reduction Performance in Polymer‐Electrolyte‐Membrane Fuel Cells. Issue 4 (22nd November 2016) - Zhang, Chao; Wang, Yu‐Cheng; An, Bing; Huang, Ruiyun; Wang, Cheng; Zhou, Zhiyou; Lin, Wenbin
Abstract : A high‐performance nonprecious‐metal oxygen‐reduction electrocatalyst is prepared via in situ growth of bimetallic zeolitic imidazolate frameworks on multiwalled carbon nanotubes (CNTs) followed by adsorption of furfuryl alcohol and pyrolysis. The networking boosts the conductivity and performance in a polymer electrolyte membrane fuel cell, yielding a maximal power density of 820 mW cm −2 .